A PERT model based on the Dampster and Shafer's theory of evidence – application to product development. (10th March 2023) - Lolli, Francesco; Coruzzolo, Antonio Maria; Zironi, Matteo
The epistemic uncertainty affecting the estimates of lead times in new product development may have significant side effects over the management of the said projects, and nowadays an effective tool to manage this kind of uncertainty is still missing for new product development projects. In this paper we propose a new project evaluation and review technique (PERT) model based on lead times defined by the theory of evidence. The main advantages of our proposal come from the inclusion and measurement of the epistemic uncertainty lying into lead time estimates along the PERT network, which is further analysed by means of Monte Carlo simulation. The work is completed by applying this model to a real instance of new product development process within a company, and the results obtained are analysed by investigating how different combination and transformation rules affect the probability distribution of the activity lead times.